Sistematización de la experiencia voto electrónico, elecciones seccionales 2014, en la provincia del Azuay desde la aceptación de la ciudadanía y organizaciones políticas en su aplicación - Valarezo Aguirre, Matilde Teresa (2016)
This systematization, analyzes the feasibility and impact of implementing the vote mail in Ecuador, as a pilot project, specifically in the Province Azuay, the result of a highly media world that generates strong demands and expectations of access to information in real time and product acceptance of the citizenship and political organizations in implementation, as a possible mechanism for future elections. The validity of the new charter in 2008, has generated a profound change in state society relations; the electoral function through National Electoral Council (CNE) in Ecuador, said that is promoting a change in the democratic matrix and in relations between political organizations and the citizenship. The implementation of electronic voting in the democratic process exercise of suffrage, is considered by the CNE as a reliable process and stay safe, effective and democratic change. To this effect, in 2014 regional elections, the CNE implemented as a pilot electronic voting plan two provinces (not entirely) Azuay and Santo Domingo de los Tsáchilas and parish in the province of Pichincha (La Morita). Among the major challenges of the Constitution is the modernization of the state, which promotes the consolidation of a State able to coordinate and regulate the economy, redistribute wealth and achieve social justice and equality, improve the weakness and void efficiency of public administration; and coordination of social agents and economic, around the goals of balanced and sustainable social development, disappear as the disarticulation between the various levels of government and the lack of democracy, transparency and citizen participation. Within this modernization, it is the transformation of the system political: it should be since the reform of the executive; reforming the structure of legislature to adapt to the new model of territorial development; autonomy power of attorney; modify the electoral system to strengthen participatory democracy; and depolarize the supervisory bodies. Another important aspect of the modernization of State is the automation of processes. The CNE argues that the application of the techniques automatic data processing has a dual purpose: Guarantee transparency of elections and accelerate those processes that handle large data volumes. But what Ecuador is ready for this change? Does electronic voting is the alternative the country needs? Will this tool or other valid when there yet autonomy of state functions? Is there a digital culture installed in the Ecuadorian citizenship? Really this tool solves transparency and autonomy of state functions?